Voluntary Assurance of Sustainability Reports: Evidence from Indonesia - Inten Meutia; Shelly F Kartasari; Rochmawati Daud (Universitas Negeri Semarang, 2022)
Purpose : This study aims to prove the determinants of the adoption of assurance statements in companies in Indonesia. Several companies in Indonesia have included assurance reports in their sustainability reports as a voluntary disclosure. This phenomenon motivates this study, considering that sustainability report assurance is gaining interest among companies, but there is still very little literature discussing this issue, specifically in Indonesia. This research will fill the research gap on sustainability report assurance. Method : Using data from companies participating in ASRRAT (Asian Sustainability Report Rating) for five years (2017 – 2021), this study assesses the influence of governance, profitability, and company age on the company’s decision to adopt assurance on sustainability reports. Total unit analysis are 140 sustainability reports from 28 companies. Findings : The results show that governance, profitability, and the company age significantly influence the adoption of assurance on sustainability reports. This study provides preliminary evidence of the willingness of companies to adopt assurance of sustainability reports in Indonesia by identifying characteristics that distinguish Indonesia from other countries concerning the choice to implement an assurance for sustainability reports. Novelty : This research uses governance measures based on the GRI standard of governance disclosure standards, consisting of 29 disclosure indicators. Previous studies linking governance with sustainability reports only tested specific governance mechanisms, such as the audit committee, board of directors, or diversity. Keywords : Assurance Statement; Corporate Governance; Sustainability Report